This Gaming Life Travels in Three Cities - Rossignol, Jim (University of Michigan Press, 2008)
"In May 2000 I was fired from my job as a reporter on a finance newsletter because of an obsession with a video game. It was the best thing that ever happened to me." So begins this story of personal redemption through the unlikely medium of electronic games. Quake , World of Warcraft, Eve Online, and other online games not only offered author Jim Rossignol an excellent escape from the tedium of office life. They also provided him with a diverse global community and a job-as a games journalist. Part personal history, part travel narrative, part philosophical reflection on the meaning of play, This Gaming Life describes Rossignol's encounters in three cities: London, Seoul, and Reykjavik. From his days as a Quake genius in London's increasingly corporate gaming culture; to Korea, where gaming is a high-stakes televised national sport; to Iceland, the home of his ultimate obsession, the idiosyncratic and beguiling Eve Online, Rossignol introduces us to a vivid and largely undocumented world of gaming lives. Torn between unabashed optimism about the future of games and lingering doubts about whether they are just a waste of time, This Gaming Life also raises important questions about this new and vital cultural form. Should we celebrate the "serious" educational, social, and cultural value of games, as academics and journalists are beginning to do? Or do these high-minded justifications simply perpetuate the stereotype of games as a lesser form of fun? In this beautifully written, richly detailed, and inspiring book, Rossignol brings these abstract questions to life, immersing us in a vibrant landscape of gaming experiences. "We need more writers like Jim Rossignol, writers who are intimately familiar with gaming, conversant in the latest research surrounding games, and able to write cogently and interestingly about the experience of playing as well as the deeper significance of games." -Chris Baker, Wired "This Gaming Life is a fascinating and eye-opening look into the real human impact of gaming culture. Traveling the globe and drawing anecdotes from many walks of life, Rossignol takes us beyond the media hype and into the lives of real people whose lives have been changed by gaming. The results may surprise you." -Raph Koster, game designer and author of A Theory of Fun for Game Design "Is obsessive video gaming a character flaw? In This Gaming Life, Jim Rossignol answers with an emphatic 'no,' and offers a passionate and engaging defense of what is too often considered a 'bad habit' or 'guilty pleasure.'" -Joshua Davis, author of The Underdog "This is a wonderfully literate look at gaming cultures, which you don't have to be a gamer to enjoy. The Korea section blew my mind." -John Seabrook, New Yorker staff writer and author of Flash of Genius and Other True Stories of Invention digitalculturebooks is an imprint of the University of Michigan Press and the Scholarly Publishing Office of the University of Michigan Library dedicated to publishing innovative and accessible work exploring new media and their impact on society, culture, and scholarly communication. Visit the website at www.digitalculture.org.